Big Mommas house 2 - Whitesel, John (Philippines : Viva Video, 2006)
Nonstop laughs are back in the house! Hot on the heels of the mega-hit Big Momma's House comes a super-sized sequel that's wilder, funnier, and more enormously entertaining than the original! In the interest of national security, FBI a gent Malcolm Turner (Martin Lawrence) goes back undercover as Big Momma - a slick-talking, slamdunking Southern granny with attitude to spare! Bow this granny must play nanny to three dyfunctionalupper-class kids in order to spy on their computer hacker dad. Bursting at the seams with lighthearted lunacy and eye-popping sight gags, Big Momma's House 2 is loads of fun for the whole family!